Hasil Belajar Kognitif Siswa dengan Pendekatan Saintifik Pada Sekolah Menengah Pertama Di Palangka Raya - Hadma Yuliani; Resa Yulianti; Mariati Mariati; Cici Herianto (Universitas PGRI Semarang, 2020)
This study aims to determine the increase in cognitive learning outcomes of students in junior high schools in Palangkaraya using a scientific approach that uses a guided inquiry learning model, CLIS (Children's Learning in Science), and experimental methods in learning physics of simple aircraft subjects. This research uses a quantitative approach and the type of research is descriptive. The instrument used was a cognitive learning achievement test. The population in this study were all junior high schools in Palangka Raya City. In taking a sample using cluster sampling techniques, namely SMP Negeri 7 Palangka Raya and MTs An-Nur Palangka Raya. The research sample is class VIII - B in SMP 7 Palangka Raya, and class VIII-A, and VIII - B for MTs An-Nur Palangka Raya. The results of the study concluded that an increase in students' cognitive learning outcomes in junior high schools in Palangka Raya after applying an approach that uses the guided inquiry learning model, CLIS, and experimental methods obtained an average N-gain in a row of 0.47; 0.57; and 0.50. So, increasing student learning outcomes in junior high schools in Palangka Raya uses a scientific approach that uses the guided inquiry learning model, CLIS, and experimental methods in learning physics in simple aircraft subjects in the medium category.